2009
DOI: 10.1007/s10561-009-9136-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence decisions by families to donate brain tissue for medical research

Abstract: Whilst mainstream transplant literature provides valuable insights into the influences on families to donate organs and tissues for transplant, the relevance of these findings in relation to organ donation for research remain speculative. The present study aims to expand the research donation literature, by exploring factors that influence a family's decision to donate brain tissue to neuroscience research. The verbal responses of the senior available next-of-kin (NOK), to the question of brain donation for re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
46
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 14 publications
6
46
1
Order By: Relevance
“…Garrick 4 reported an acceptance rate of 54% in researchrelated donations of brain tissue. An Australian study 3 reported 58% acceptance rates; the main reasons were the desire to help others and open dialogue within the family about the organ donation process.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Garrick 4 reported an acceptance rate of 54% in researchrelated donations of brain tissue. An Australian study 3 reported 58% acceptance rates; the main reasons were the desire to help others and open dialogue within the family about the organ donation process.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,12 Although the apparently low number of whole-brain donations could indeed reflect this reluctance by Brazilian families, such interpretations should be made with caution. This is still an early case series, with substantial room for change.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Much of what is already known about this comes from Australian research that evaluated the responses of next-of-kin to a telephone request made on the day of the necropsy to donate the brain of the deceased (Azizi et al 2006;Garrick et al 2009;Sundqvist et al 2012).…”
Section: Discussionmentioning
confidence: 99%